TRANFORMASI TEKS NASKAH LAWAN CATUR KARYA KENETH SAWYER GOODMAN - Yonaldi, Deyon Afri; Elmustian, Elmustian; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The performing arts of drama develop in the midst of society, so that drama has become an inseparable part of people's lives. In addition, other forms of drama performance art also involve other arts such as: dance, music, fine arts, drama performing arts have an important role in shaping a character. It is this character that is developed into the message the writer sends to the reader. Sometimes in drama performing arts, the creative process resulting from the thought process (text / script) is not always in line with its meaning with the activities that occur on stage. This is called transformation. Text transformation is an action or creative process carried out by art actors to produce a new work. In literary works, text transformation has different types, including the transformation of the text of oral literary works to writing, the transformation of written to oral literary works, or written to written literary works, although they have many varieties or forms of text transformation have the same goal of adding to the essence. -esensi in the literary work itself in and broadens the imaginary space of the literary audience.Key Words: Text Transformation, Drama